Assessment of heavy metal contamination in groundwater of rural areas of Kurdistan Province Iran: A comprehensive study - Payam Younesi Baneh; Borhan Ahmadi; Hamzeh Salehzadeh; Hady Mohammadi; B. Shahmoradi; Bayazid Ghaderi (Heliyon)
This study focuses on the contamination of groundwater by heavy metals (HMs) in the Kurdistan Province of Iran, an area heavily reliant on these water resources, especially in rural regions. This research aimed to quantify the concentrations of 20 HMs in groundwater sources and assess the associated health risks, including both carcinogenic and non-carcinogenic effects, for different age groups. The study was conducted in 2024. We collected 155 groundwater samples from water resources of the villages in Kurdistan Province, west of Iran. The study encompassed comprehensive sampling of groundwater from various wells and springs throughout the province, which was subsequently subjected to thorough laboratory analysis utilizing Inductively Coupled Plasma Mass Spectroscopy (ICP-MS) for the quantification of heavy metal (HM) concentrations. The highest concentrations of As, Co, Cu, and Mo were 7.90, 0.22, 2.48, and 1.68 μg/l, respectively. It was related to the cities of Qorveh, Sanandaj, Baneh, and Qorveh respectively. A Health Risk Assessment (HRA) was performed, indicating that, while the concentrations of most HMs were within the thresholds established by national and international standards, certain metals, such as arsenic and lithium, presented notable non-carcinogenic risks, especially to children. These metals were responsible for over 48 % of the cumulative hazard index (HI) across all ten cities evaluated. Furthermore, the HI for the adult demographic exceeded 1.0 (specifically 1.23) exclusively in Qorwe city. The study also identified a high carcinogenic risk associated with lead across the province, which has a carcinogenic risk of 7.3 × 10−03 in 10 studied cities, which is more than the guideline value of 10−04. The findings underscore the urgent need for continuous monitoring and the implementation of preventive measures to safeguard public health. The results provide crucial insights for policymakers and health authorities, facilitating informed decisions to mitigate the health risks posed by HM contamination in the region's groundwater.